Population trends and migration routes of the East Asian Bean Goose Anser fabalis middendorffii and A. f. serrirostris - Li, Chang; Zhao, Qingshan; Solovyeva, Diana; Lameris, Thomas; Batbayar, Nyambayar; Bysykatova-Harmey, Inga; Li, Hansoo; Emelyanov, Vladimir; Rozenfeld, Sonia B.; Park, Jinyoung; Shimada, Tetsuo; Koyama, Kazuo; et al. (Wildfowl, 2020)
Our ability to define the population status, migration routes and seasonal distribution of Bean Geese Anser fabalis throughout the annual cycle in East Asia is severely compromised by the presence of two subspecies (Eastern Taiga Bean Goose A. f. middendorffii and Eastern Tundra Bean Goose A. f. serrirostris), which are difficult to differentiate in the field. In this analysis, using tracking data from telemetry-tagged geese, count survey data and expert knowledge, we attempt to update existing knowledge of the ranges covered by both subspecies of Bean Goose in East Asia. We suggest that, in summer, the Eastern Tundra Bean Goose ranges from the Taimyr Peninsula in the west to the Anadyr River in the east. Taiga Bean Geese breed further south in the taiga zone, and results indicate that they occur in north-western Mongolia, Yakutia and the Kamchatka Peninsula during the summer months. The winter distribution of both subspecies extends through China, Japan and South Korea. Tracking data from 154 individuals revealed a major overlap in the migration routes of Tundra Bean Geese wintering in China, South Korea and Japan, but discrete flyways for Taiga Bean Geese wintering in different regions. Long-term ground surveys carried out in the wintering range showed that numbers of Bean Geese in China and South Korea have increased significantly, to number 253,100 and 88,300 individuals respectively, of which roughly 10% are considered to be Taiga Bean Geese, about which subspecies we need to know more. Numbers of Japanese-wintering Bean Geese are slowly rising, currently numbering c. 10,300 (c. 900 Tundra Bean Geese and c. 9,400 Taiga Bean Geese). On the basis of these national and flyway estimates, derived from counts over the last five years, we identify new key wintering sites for the species in East Asia. Distributional changes at sites in China showed that wintering Bean Geese (most likely of the Tundra form) have become more widespread and numerous in the Yangtze River floodplain since the early 2000s. We argue for future strengthening of international cooperation to continue tracking and monitoring of Bean Geese, to provide a sound scientific basis for the effective management and protection of the flyway populations of both Bean Goose subspecies throughout East Asia.